Analisis Kepemimpinan Digital (Digital Leadership) di Emado’s Shawarma Kopo Bandung - Widiaty Nur Khofifah; Annisaa Siti Shalihah; Neng Titin Rodiah; Astria Aulia Dewi; Ai Alika (INDO PUBLISHING, 2026)
The rapid development of digital technology, particularly after the Covid-19 pandemic, has pushed organizations across various sectors to adapt, including the food and beverage (F&B) industry. This situation demands leadership capable of integrating digital technology into the organization's operational processes, known as digital leadership. This study aims to analyze the implementation of digital leadership at Emado's Shawarma Kopo, Bandung, with a focus on technology integration, supervision and support for team performance, adaptability in digital transformation, and orientation towards organizational goals and results. This study uses a qualitative approach with descriptive methods. Data were obtained through in-depth interviews with key informants, namely the Store Manager of Emado's Shawarma Kopo, and supported by documentation studies. Data analysis was conducted using content analysis and narrative analysis with reference to the Miles and Huberman model. The results show that digital leadership has been implemented through the use of integrated digital systems, data-based performance monitoring, regular training for employees, and decision-making oriented towards achieving targets. The implementation of digital leadership has been proven to improve work efficiency, employee professionalism, and sales performance. This study is expected to provide theoretical contributions and serve as a practical reference for F&B businesses.